2021
DOI: 10.1590/1984-0462/2021/39/2019226
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Impact of Probiotics on Nonalcoholic Fatty Liver Disease in Pediatrics: A Systematic Review

Abstract: Objective: Evaluate the effects of probiotics use, compared with placebo, in pediatric patients with non-alcoholic fatty liver disease (NAFLD), using laboratorial and ultrasonographic parameters as outcomes. Methods: A systematic review of the literature was performed through MEDLINE and Lilacs databases. The articles selected were randomized controlled clinical trials published until November 2018, without any language restriction, dealing with pediatric patients with NAFLD. Patients were divided into 2 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The possible beneficial effect of probiotics is based on gut microbiota manipulation with a subsequent positive outcome in the gut‐liver axis (13,14). Specifically, the coadministration of probiotics, vitamins, and prebiotics seems to result in a more “liver protective” intestinal microbiota by regulating bile acid composition, glucose, and fat metabolism and reversing the liver damage in patients with NAFLD (26,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible beneficial effect of probiotics is based on gut microbiota manipulation with a subsequent positive outcome in the gut‐liver axis (13,14). Specifically, the coadministration of probiotics, vitamins, and prebiotics seems to result in a more “liver protective” intestinal microbiota by regulating bile acid composition, glucose, and fat metabolism and reversing the liver damage in patients with NAFLD (26,28).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies examining probiotic supplementation in children with NAFLD have shown promising results (8)(9)(10)(11). Modification of the gut microbiota with probiotics might have a positive effect in the management of pediatric NAFLD (12)(13)(14). To elucidate this, we conducted a systematic review and meta-analysis in an effort to clarify the role of probiotics in the management of pediatric NAFLD.…”
Section: What Is Newmentioning
confidence: 99%